(untitled) - Johnson, George B. (3rd ed., 2009)
A student favorite, this engaging text, now presented with a new single column format, is rich with student-oriented applications and illustrations that drive the learning. Written from scratch to be an appealing and accessible learning tool with an emphasis on "how things work and why things happen the way they do", this Essentials text features a straightforward, clear writing style with ample use of analogies to help students relate new material to familiar things. NEW digital assets for the 3rd edition include high interest video clips and animations of key biological concepts.
Keywords: Biology,Sinh học; Textbooks,Sách giáo khoa